If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(1/3)*x-2 = (-5/3)*x-(3/4) // - (-5/3)*x-(3/4)
(1/3)*x-((-5/3)*x)+3/4-2 = 0
(1/3)*x+(5/3)*x+3/4-2 = 0
2*x-5/4 = 0 // + 5/4
2*x = 5/4 // : 2
x = 5/4/2
x = 5/8
x = 5/8
| 3y+7=2y+1y | | 485-230-(2+42)5=g | | 45=(x+8)(3x-3) | | 0.25h+4=0.25 | | -6(3*-8)=-6 | | 1/5(12+j)=25 | | 7(6f+-3)+-6= | | -7(3x-8)+3=-21x+59 | | AB=x+8 | | 2/3(12x-18) | | 2z-12-14= | | y^2+10y+3=0 | | 1500=-50p | | -2/5-1/3x=-1/2 | | x^2+4+16=0 | | w/w-4-2w/2w-5=w-2/2w^2-13w+20 | | 6.21(1-7.8r)=-24.20764+75R | | -2(2x-8)=4x+16 | | -3r+34=4r-15 | | x^3+4x^2+7x+28=0 | | 106-(7x+4)=7(x-6)+x | | 90/4 | | 12-3/4(x+15)=4 | | -3/2=7/2w-8/3 | | -10(-6w+-5)+5w= | | 2y+-7+5y=0 | | 3/7y=-33 | | y/6-3.5=-22.7 | | (x-5)=-4 | | 44+n=22 | | -1/2y+1/5=-1/7 | | x(m+2)+y(m-2)=z(m-7)form |